The Black Sea economic cooperation zone: Outline of a new community of states - Werner Gumpel (Intereconomics, 1993)
The political changes in eastern Europe have opened up new opportunities for trade among the countries surrounding the Black Sea, and especially between the former socialist countries and Turkey, the country with the longest Black Sea coastline. The following article describes the present stage of economic cooperation reached by the countries concerned and analyzes the prospects for the future.
Keywords: 330; Integration